Kemampuan Siswa Menulis Teks Eksposisi Kelas VIII Sekolah Menengah Pertama - Agung Hidayat; Jamilin Tinambunan (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The problems discussed in this study are How Students' Ability to Write Exposition Text Based on Exposition Text Structure and How Students' Ability to Write Exposition Text Based on Linguistic Rules of Exposition Text. This study aims to describe, analyze, interpret, and conclude information and data about the ability to write expository texts based on the structure and linguistic rules of exposition texts for class VIII students of SMP Negeri 1 Sungai Apit District, Siak Sri Indrapura Regency, Academic Year 2022/2023. The population in this study were all students of class VIII.4, totaling 28 people. The sample used is a saturated/full sample. The results of the research on students' ability to write exposition texts are based on the structure and rules of exposition texts. The method used in this research is descriptive and quantitative research approach. Writing exposition texts based on the exposition text structure is in the sufficient category (69.34), writing exposition texts based on exposition language rules is in the sufficient category (70). It can be concluded that the average ability of students to write exposition texts for Class VIII SMP Negeri 1 Sungai Apit District, Siak Sri Indrapura Regency for the 2022/2023 Academic Year is 69.67 which is categorized as sufficient and the hypothesis is accepted.